Peningkatan Proses Pembelajaran Tentang Luas Bangun Melalui Model Kooperatif Stad dan Kuis pada Siswa Kelas VI SDN Tumbang Titi - Sudirman Sudirman (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2021)
This study aims to carry out the dynamics of online-based learning in the midst of a pandemic that has not been optimal, especially in dealing with the Covid-19 situation, the tools used are cellphones / laptops. Efforts made to overcome this problem are to determine the dynamics of online learning in the midst of a pandemic. The purpose of the implementation is to find out the problems and follow-up of the problems faced by the school, which currently requires all teaching and learning processes for students to be temporarily carried out at home. Sources of research data are class X students and class XI students to fill in school teaching and learning activities to take learning policies that are carried out over long distances with two categories, namely the Online model and the Offline model. The results of the study show that the dynamics of online learning applied in SMAN 1 Intertwine by 75% online distance learning, and 25% offline learning